Job levels and wages - Christian Bayer; Moritz Kuhn (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Job levels summarize the complexity, autonomy, and responsibility of task execution. Conceptually, job levels are related to the organization of production, are distinct from occupations, and can be constructed from data on task execution. We highlight their empirical role in matched employer-employee data for life-cycle wage dynamics, refine a task-based view of wage determination, and demonstrate that differences in job levels account for most of the observed wage differences. We also show, within a structural framework, that a job-level perspective provides a novel and fruitful interpretation of widely studied phenomena such as the gender wage gap and the returns to education and seniority.
Keywords: D33; E24; J31; 330; job levels; wage structure; career ladder